Pengaruh Jumlah Sirip Heatsink Terhadap Distribusi Temperatur Pada Alat Penghasil Air Dari Udara Atmosfir - Ben Tarigan; Muhamad Jafrim; Sadrak Ndollu (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2021)
Water is a natural resource that is absolutely necessary for human life and in an environmental systems, water is an element of the environment. Water demand is the amount of water needed for household, industrial, urban flushing and others. One of the water-producing systems that is being developed at present is the technology of producing water from the atmosphere. This technology is desirable to condense water vapor. The amount of condensed water is proportional to the amount of heat transferred, which is related to the thickness of the layer and the temperature difference between the steam and the surface. The purpose of this study was to determine the effect of the number of heat sink fins on the temperature in the box in a water-generating technology device from atmospheric air. Variation of heat sink fins, namely 4 fins, 6 fins, 8 fins with an angle of 750. The test results show that the number of heat sink fins has an effect on the temperature distribution of each test point in the space of atmospheric water producing technology.